Identifikasi Problem Penyusunan Modul Ajar di MTs Al-Islam Joresan Ponorogo - Asyaffaratamananda Janatus Salsabila; Isabelle Rochat (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
This research aims to identify problems that arise in the implementation of teaching modules in the Independent Curriculum at MTs Al-Islam Joresan Ponorogo. In an era of increasingly selective education, the quality of education is a matter of great concern, including in the management of the curriculum and teaching modules. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that teachers experience difficulties in developing teaching modules that are effective and in accordance with the principles of the Independent Curriculum, especially in implementing the Pancasila Student Profile (P5). These challenges include suboptimal understanding of the new curriculum, limited resources, and variations in the level of difficulty of the material taught. To overcome this, it is recommended that seminars, mentoring and group discussions be held to strengthen teachers' understanding in developing relevant and contextual teaching modules. It is hoped that this research can contribute to the preparation of better teaching modules that suit the needs of students.